Ecological correlates of Golden Eagle Aquila chrysaetos breeding occurrence in Sardinia. Issue 4 (1st October 2020) - Di Vittorio, M.; Medda, M.; Sirigu, G.; Luiselli, L.; Manca, G.; Nissardi, S.; Zucca, C.; Ruiu, D.; Brau, A.; Sanna, M.; Grussu, M.; Campus, A.; et al.
ABSTRACT: Capsule: Golden Eagles Aquila chrysaetos in Sardinia are clustered across the main mountain ranges of the island, with a preference for undisturbed and homogeneous inland habitats. Aims: To analyse habitat preferences of the Golden Eagle in Sardinia, Italy, at the landscape and home range spatial scales. Methods: Landscape scale habitat preferences were analysed using the 10 × 10 km Universal Transverse Mercator grid and the home range scale was based on the spatial distribution of breeding territories. Generalized linear models were fitted with three different sets of environmental predictors (topographic, bioclimatic and land use variables) to analyse the spatial distribution of Golden Eagles with a case–control design. Results: Eagles showed a preference for rugged and elevated areas, characterized by a certain degree of humidity and surrounded by areas of forest. The distribution of Golden Eagles on this Mediterranean island was negatively affected by the occurrence of arable farmland and coastal areas, as well as by the effects of habitat fragmentation. Conclusions: The results of this study could contribute to future management strategies and conservation projects aimed to protect this species, and may be used to identify the most suitable conservation areas for this and other competing species, such as the Bonelli's Eagle Aquila fasciata, which is currently the subject of a reintroduction project in Sardinia.